Exon junction complexes suppress spurious splice sites to safeguard transcriptome integrity - Böhm, Volker; Britto-Borges, Thiago; Steckelberg, Anna-Lena; Singh, Kusum K.; Gerbracht, Jennifer V.; Gueney, Elif; Blazquez, Lorea; Altmüller, Janine; Dieterich, Christoph; Gehring, Niels H. (Molecular cell, 2018)
Productive splicing of human precursor messenger RNAs (pre-mRNAs) requires the correct selection of authentic splice sites (SS) from the large pool of potential SS. Although SS consensus sequence and splicing regulatory proteins are known to influence SS usage, the mechanisms ensuring the effective suppression of cryptic SS are insufficiently explored. Here, we find that many aberrant exonic SS are efficiently silenced by the exon junction complex (EJC), a multi-protein complex that is deposited on spliced mRNA near the exon-exon junction. Upon depletion of EJC proteins, cryptic SS are de-repressed, leading to the mis-splicing of a broad set of mRNAs. Mechanistically, the EJC-mediated recruitment of the splicing regulator RNPS1 inhibits cryptic 5′SS usage, while the deposition of the EJC core directly masks reconstituted 3′SS, thereby precluding transcript disintegration. Thus, the EJC protects the transcriptome of mammalian cells from inadvertent loss of exonic sequences and safeguards the expression of intact, full-length mRNAs.
Gesehen am 02.04.2020